2021
DOI: 10.11591/ijeecs.v21.i2.pp945-956
|View full text |Cite
|
Sign up to set email alerts
|

Energy budget and methods for determining coordinates for a radiomonitoring system based on a small spacecraft

Abstract: The existing ground-based radio monitoring systems do not allow performing the functions and tasks of radio spectrum monitoring in a quality manner. Therefore, to improve the efficiency of the radio spectrum monitoring systems for countries with a large territory, such as the Republic of Kazakhstan, it is proposed to use low-orbit small spacecrafts as radio monitoring stations. The analysis of the energy budget of radio lines on the basis of existing radio electronic means on the territory of the Republic of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In this regard, an inexpensive solution for accelerating neural computing is the use of FPGAs [27]. In general, the computing resources of FPGAs in the implementation of artificial neural networks can also be applied to the processing of other signals, especially onboard low-orbit satellites [28,29].…”
Section: Discussion Of the Results Of Evaluating The Accuracy Of Huma...mentioning
confidence: 99%
“…In this regard, an inexpensive solution for accelerating neural computing is the use of FPGAs [27]. In general, the computing resources of FPGAs in the implementation of artificial neural networks can also be applied to the processing of other signals, especially onboard low-orbit satellites [28,29].…”
Section: Discussion Of the Results Of Evaluating The Accuracy Of Huma...mentioning
confidence: 99%
“…In [16], an analysis of the energy budget of radio lines was carried out, and the analysis showed the possibility of applying a low-orbiting small spacecraft to fulfil radio monitoring. The analysis of the signal level at the input of the measuring onboard receiver of the radio monitoring system showed that for most ground-borne radio-electronic means, the signal-to-interference ratio is more than 10 dB, which is acceptable for satellite radio monitoring systems.…”
Section: Methodsmentioning
confidence: 99%
“…In the framework of the existing ground-borne means of radio monitoring, it is impossible to qualitatively carry out the functions and problems of radio monitoring. One of the directions for improving the effectiveness of radio monitoring systems is to study the possibility of using loworbiting small spacecraft (SS) as radio monitoring stations [16]- [21]. Such systems possess a range of advantages, including high efficiency, a global view, and total coverage of the territory.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations are primarily due to the fact that if it is impossible to describe mathematically the process generating the desired signal, then it becomes impossible to use the Kalman filter. Also a weak link is the similarity coefficient, which has proven itself very well for the processes described by equation (1). But in the considered process, it was assumed all the time that the amplitude of the desired signal does not change.…”
Section: Investigation Of the Dependence Of The Decision-making Speed...mentioning
confidence: 99%
“…In [1], an analysis of the signal levels at the input of the receiver of the radio monitoring system was carried out, which showed that for most of the considered ground-based radio electronic means, the SNR ratio is greater than 10 dB, which is acceptable for radio monitoring on the basis of a small satellite. However, it is noted in the work that for the effective operation of the radio monitoring system based on the small satellite it is necessary to apply special methods of processing weak signals, the use of on-board receivers with increased sensitivity and antennas with increased gain.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%